Taste Panel Evaluation and Acceptance of Soy-beef Bur~er - Babji, Abdul Salam; Abdullah, Aminah; Yusuf, Fatimah (1986)
This study was conducted to investigate the effect of the addition of textured soy protein (TSP) at 0%, 20%, 30%, 40% and 50% levels on the quality and general acceptance of soy-beef burgers by trained taste panels as well as the consumer. Analyses carried out at three-week intervals include TBA values, water holding capacity, cooking loss, sensory evaluation and consumer acceptance. The increase of textured soy protein levels in beef burger resulted in significant decrease in TBA values and cooking loss. The addition of textured soy protein also increased the water holding capacity of the products. Generally, storage time reduced the quality of these products. Sensory properties showed that the substitution of meat with textured soy protein increased the intensity of beany flavour and taste. The addition of textured soy protein decreased the colour acceptance but had no specific effect on the quality attributes such as appearance, texture, saltiness and juidness of the product. Results of the consumer acceptance test showed that there were no significant differences in preference for the 0%,20% and 30% levels of textured soy protein in beef burger.